1989
DOI: 10.1007/bf00402560
|View full text |Cite
|
Sign up to set email alerts
|

Plasma progesterone concentration and reproductive function relative to thyroid activity in postpartum buffaloes (Bubalus bubalis)

Abstract: The lowest value for plasma protein bound iodine (PBI) (3.47 micrograms %) in 20 freshly calved Murrah buffaloes was observed on day 1 postpartum. The values then increased consistently up to day 36 and were almost constant thereafter. The plasma progesterone concentrations were lower in animals with relatively low PBI from day 22 to 57 postpartum, except on day 36. The mean values +/- SE (ng/ml) in the high and low PBI groups were 0.93 +/- 0.09 and 0.72 +/- 0.15. The correlation coefficient between PBI and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In some reports (Kamonpatana, [22], Prakash and Madan, [27], Momongan, et al, [23], Eissa, et al, [28] and Tiwari, et al, [31]) basal values 0.1-0.6 ng/ml were reached during calving suggesting complete luteolysis at parturition, with no significant changes during the postpartum period. In the others decline of progesterone continued during the postpartum period to reach minimum levels on day-6 (Bahga and Gangawar, [32] and Bahga, [33]) to day-15 (El-Belely, et al, [24]), indicating complete regression of the corpus luteum of pregnancy was reported by Pahwa and Pandey, [34]. Demise of the corpus luteum after calving expressed by progesterone concentration on Day-3 postpartum was no different in milked and suckled buffaloes (Arya and Madan, [35]).…”
Section: Discussionmentioning
confidence: 99%
“…In some reports (Kamonpatana, [22], Prakash and Madan, [27], Momongan, et al, [23], Eissa, et al, [28] and Tiwari, et al, [31]) basal values 0.1-0.6 ng/ml were reached during calving suggesting complete luteolysis at parturition, with no significant changes during the postpartum period. In the others decline of progesterone continued during the postpartum period to reach minimum levels on day-6 (Bahga and Gangawar, [32] and Bahga, [33]) to day-15 (El-Belely, et al, [24]), indicating complete regression of the corpus luteum of pregnancy was reported by Pahwa and Pandey, [34]. Demise of the corpus luteum after calving expressed by progesterone concentration on Day-3 postpartum was no different in milked and suckled buffaloes (Arya and Madan, [35]).…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid hormones in buffalo ( Bubalus bubalis ), as well as in other species, influence reproductive efficiency. A previous study observed a correlation between plasma protein-bound iodine and follicular development interval, postpartum estrus interval, service period, and number of inseminations for conception 4 . Thyroid hormones are also important for the growth and development of the mammary gland and for increasing milk production 5,13 .…”
Section: Introductionmentioning
confidence: 98%
“…A previous study observed a correlation between plasma protein-bound iodine and follicular development interval, postpartum estrus interval, service period, and number of inseminations for conception. 4 Thyroid hormones are also important for the growth and development of the mammary gland and for increasing milk production. 5,13 However, the importance of thyroid hormones in postpartum metabolism of buffalo requires further investigation.…”
Section: Introductionmentioning
confidence: 99%